Secularism in the West between the Dialectic of Religion and the Material Positivism - Benaoun, Tayeb (Milev Journal of Research and Studies, 2022)
Secularists believe that the mundane life evaluation is only up to the rational principles, which are based on the independence of the mind, which is based on two axes of principles; Principles necessary to ensure the independence of the human mind, and other principles necessary to ensure the independence of the human being as a moral agent, all of which are incompatible with the non-secular system. The research aims to limit the term in the bosom of its Western origins away from Arab influence. And to reveal its transformations and extremist goals. From a descriptive analytical perspective in order to clarify and achieve the panoramic picture of the various historical events and scenes that established the dynamic concepts of the Western mind..